An Evaluation of the Architecture and Urban Positioning of the Phaselis Aqueduct - Kibar Cesur; Leyla Kaderli (Phaselis: Disiplinlerarası Akdeniz Araştırmaları Dergisi)
Abstract: The Phaselis Aqueduct, constructed in the IInd century AD to address the increaing population and water demands, stands as an advanced example of Roman engineering, contributing significantly to the social, economic, and public life of Phaselis. Designed to align with the city’s topography, the aqueduct transported water from distant sources, to the city, delivering it through two directional shifts to baths, fountains, an other public spaces. In the Late Antique Period, the aqueduct was adopted to the city’s evolving urban plan through various repairs and reinforcements, enabling its contiuned use. However, it gradually deteriorated due to eartquakes and changes in sea levels. The structural features of the Phaselis aqueduct, its technical details and its contribution to the city’s water transmission system have not been comprehensively documented due to partial investigations in the past. For this reason, a detailed documentation process was initiated and the relationship of its system to the structures in different parts of the city was examined through the provision of architectural and engineering documentation. Only limited sections of the aqueduct have survived to the present day, and the non-existing sections of the aqueduct have been reconstructed with their possible locations according to the data obtained.